P7 Standardised procedure trollies save time and stress – a qi project. (12th March 2018) - Maxted, D; Dewar, A; Moran, M
Abstract : Introduction: Basic procedures such as phlebotomy and cannulation are commonly performed in children admitted to hospital by junior doctors. In our tertiary teaching hospital, children are admitted to one of seven wards after initially been seen on the admission unit. Out of hours junior doctors cover a number of wards, often attending wards not worked on in-hours. We highlighted a problem that finding equipment was frequently proving difficult and an in-effective use of time; partly due to varying equipment locations on each ward. We set out to streamline the process by using a standardised procedure trolley. Methods: We surveyed junior doctors to identify equipment that would be used frequently enough to form our prototype trolley. We then timed junior doctors finding a list of equipment using the prototype trolley, and without the trolley on a ward they were familiar working on and on a ward they haven't been before. Following this we agreed with ward managers to roll out the standard trolley to five wards. Results: Junior doctors on unfamiliar wards found the required equipment after an average of 10 min 13 s (6 min 28–15 m 26). On a familiar ward this reduced to 5 min 31 s (2 m 49–9 m 18). Using our prototype trolley the average reduced further to 1 min 35 s (1 m 24–1 m 46). On our unit, 30 procedures were carried out in 24 hours; over 200 in a week. Reducing the average time from 8 min 17 s (combing unfamiliar and familiar results) to 1 min 35 s would save 6 min 42 s per procedure. This would result in over 20 hours of junior doctor time saved in a single week. Post roll out audit found 3 to be well stocked, 1 to be adequately stocked and 1 poorly stocked. This correlates with our survey of doctors; just over a third felt trollies didn't have enough equipment stocked on it. 94% felt the trollies saves time when stocked! Conclusions: We highlighted a problem with undertaking a common procedure in our patients. We designed a solution, tested its efficacy and engaged stakeholders in its implementation. We have shown how a simple solution could save over 20 hours of junior doctor time a week, improving not only patient care but junior doctor satisfaction.